4 - A Few Good Men in a World of Gangsters: Discourses of Respectability and Risk amongst Student Teachers in the Western Cape, South Africa - Fiona Larkan; Brian van Wyk (African Sociological Review, 2016)
This paper considers the concurrent discourses of risk and respectability which are prominent in South Africa’s Western Cape region and asks how one becomes a ‘respectable’ man in a community which values strong masculine role models and in which there are endemic levels of violence. Through a process of risk ‘mapping’ we explore the means through which a group of young male student teachers consciously ‘locate’ risk in their built environment. We look at the strategies these young men use to negotiate risk in their lives, and the close connection between risk and respectability which they articulate on an ongoing basis.